Background to the 2nd International Symposium on Arthrogryposis. Issue 5 (July 2017) - Lester, Ruth; Hall, Judith G.; Pontén, Eva; van Bosse, Harold J.P.
Abstract : Arthrogryposis multiplex congenital is a relatively uncommon condition, with little consensus on treatment. In 2007, the 1st International Symposium on Arthrogryposis was held in Birmingham, United Kingdom, to bring together patients, their families, and a multinational group of health care experts in the field of arthrogryposis, to discuss various aspects of the care of patients with arthrogryposis multiplex congenital. From that meeting, there was a coalescence of thought on diagnosis and classification, a sharing of practices on treatments and their outcomes, and an agreement on future directions. At the beginning of the 2nd International Symposium on Arthrogryposis held in Saint Petersburg in September 2014, Russia, these "lessons learnt" were synopsized to set the tone for the new meeting.